Investigation of Spatial and Cultural Features in Contemporary Qatari Housing - Asmaa Al-Mohannadi (19418932) (2023)
Housing is a basic human need and a fundamental component of settlement status. The architectural form and spatial provisions of housing evolve in line with—and transform to meet—a specific era’s needs. Globalization has been responsible for changing the nature of housing in Qatar over the last thirty years. It has led to a standardization of construction methods and built form, representing a dramatic departure from past models of vernacular residential architecture. In light of these challenges, the ultimate purpose of this study is to explore the spatial and cultural features in a small sample of contemporary housing in Qatar. It explores the spatial layout of four Qatari residential villas to assess the social and cultural roles in contemporary housing models against the background of previous research. In the study, the authors utilized space syntax as an analytical tool to demonstrate patterns of visibility and room relations in the samples to understand occupants’ system of activities in the contemporary domestic setting, deploying visibility graph analysis (VGA) and relational graphs. Key findings include the interpretation of the probable relation to socio-cultural factors such as gender roles, hospitality, and privacy. Hence, this study fills gaps in knowledge about Qatari and Middle Eastern housing today. Other Information Published in: Urban Science License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/urbansci7020060